Presidential Term Limit as an Implicit Unamendable Provision In Indonesia's Hyper-Presidentialism - Muhammad Fathi; Anshul Tripathi (Fakultas Hukum Universitas Lampung, 2025)
This article analyzes the paradox between Indonesia’s presidential term limits and the persistence of hyper-presidentialism through a normative juridical approach structured in three stages. First, it interprets Article 7 and Article 37(5) of the 1945 Constitution using grammatical, historical, and teleological methods to assess whether term limits function as implicit eternity clauses. Second, it examines Constitutional Court rulings, including Decision No. 91/PUU-XVIII/2020 and decisions related to the 2024 election, to evaluate how term-limit norms are applied, contested, or strategically used in practice. Third, it situates these legal developments within broader political dynamics, including coalition-building, party co-optation, executive influence over judicial appointments, and the rise of political dynasties. These stages are supported by doctrinal literature on constitutional unamendability and executive aggrandizement. The analysis shows that although the two-term limit is normatively framed as an implicit safeguard against authoritarianism, its effectiveness ultimately depends on the strength of institutional autonomy. In weak institutional settings, it becomes susceptible to erosion through dynastic hyper-presidential practices.